Contagious Health Risk and Precautionary Social Distancing - Giese, Helge; Gamp, Martina; Stok, F. Marijn; Gaissmaier, Wolfgang; Schupp, Harald T.; Renner, Britta (Frontiers in Psychology, 2021)
Background: Since humans are social animals, social relations are incredibly important. However, in cases of contagious diseases such as flu, social contacts also pose a health risk. According to prominent health behavior change theories, perceiving a risk for one’s health motivates precautionary behaviors. The ‘behavioral immune system’ approach suggests that social distancing might be triggered as a precautionary, evolutionarily learned behavior to prevent transmitting contagious diseases through social contact. This study examines the link between personal risk perception for an infectious disease and precautionary behavior for disease-prevention in the context of social relationships. Methods: At two-week intervals during the first semester, 100 Psychology freshmen indicated their flu risk perception, whether they had been ill during the previous week, and their friendships within their freshmen network for eight time points. Results: Social network analysis revealed that participants who reported a high flu risk perception listed fewer friends (B = -0.10, OR = 0.91, p = .026), and were more likely to be ill at the next measuring point (B = 0.26, OR = 1.30, p = .005). Incoming friendship nominations increased the likelihood of illness (B = 0.14, OR = 1.15, p = .008), while the reduced number of friendship nominations only marginally decreased this likelihood (B = -0.07, OR = 0.93, p = .052). Conclusions: In accordance with the concept of a ‘behavioral immune system’, participants with high flu risk perception displayed a social precautionary distancing even when in an environment, in which the behavior was ineffective to prevent an illness.